ESG ratings in Poland: Are they Worth Consideration by Investors and Banks? - Zbigniew KORZEB; Paweł NIEDZIÓŁKA (Communications of International Proceedings, 2021)
The aim of this paper is to review ESG ratings assigned to Polish companies by the leading Polish market entities specializing in this area, i.e. Sustainalytics and MSCI. Due to the small sample size, the statistical approach was replaced by a simple differential analysis between the centiles of the distribution of credit ratings and ESG ratings and then between the ESG ratings of the above-mentioned entities. The number of Polish companies with the ESG ratings is very low, also when compared to other European economies. As many as 36% of the ESG-rated companies are commercial banks, with some having ESG ratings from up to 4 providers. With the exception of one company, ESG risk scores have stayed the same or improved since the rating was issued, but they are still low compared to the industry. Referring to Sustainalytics data, only 20% of Polish companies belong to the group of 15% of entities with the best ratings within a given industry. The conducted centile differential analysis indicates a lack of convergence between external credit ratings and ESG ratings as well as between the ESG ratings assigned by Sustainalytics and MSCI.
Keywords: ESG; Rating Agency; Reputation; Banking Risk; Investment Risk.